2003
DOI: 10.1037/0002-9432.73.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to posttraumatic growth: A proposed structural equation model.

Abstract: With the current shift to include positive outcomes of trauma, this research was designed to explore factors that allow growth to occur. Structural equation modeling was used to test a model for understanding posttraumatic growth. A sample (N = 174) of bereaved HIV/AIDS caregivers completed questionnaires. Spirituality, social support, and stressors were found to have a positive relationship with growth. Facilitation of posttraumatic growth is crucial to all helping professions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
162
1
13

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(199 citation statements)
references
References 66 publications
23
162
1
13
Order By: Relevance
“…In addition to these factors, personality factors such as extraversion and openness to experience (Feder et al, 2008;Tedeschi & Calhoun, 1996) and social support (Cadell, Regehr, & Hemsworth, 2003;Dunn et al, 2011;Park et al, 1996) have been positively associated with reported growth.…”
Section: Factors Related To Reported Growthmentioning
confidence: 99%
“…In addition to these factors, personality factors such as extraversion and openness to experience (Feder et al, 2008;Tedeschi & Calhoun, 1996) and social support (Cadell, Regehr, & Hemsworth, 2003;Dunn et al, 2011;Park et al, 1996) have been positively associated with reported growth.…”
Section: Factors Related To Reported Growthmentioning
confidence: 99%
“…Bereaved caregivers (HIV/AIDS) were the subjects of a study by Cadell et al (2003). In this study, spirituality, social support, and stressors were found to have a positive relationship to personal growth.…”
mentioning
confidence: 99%
“…It has been argued that stress provides a context conducive to personal development in adulthood (Aldwin 1994). Many authors have used the notion of posttraumatic growth to conceptualize the process by which people describe positive change as having resulted from trauma or crisis (Cadell et al 2003;Davis and McKearney 2003;Sears et al 2003;Tedeschi et al 1998).…”
mentioning
confidence: 99%
“…Les participants à cette recherche qualitative ont été choisis à partir d'une étude quantitative (Cadell 2001;2003;Cadell, Regehr & Hemsworth 2003). Pour répondre au questionnaire de l'étude quantitative, chaque participant devait avoir pris soin de quelqu'un qui est mort des causes liées au VIH-sida.…”
Section: La Méthodologie Les Participantsunclassified
“…(Nord 1996a(Nord , 1996b(Nord , 1997(Nord , 1998Shernoff 1997a). Les personnes ayant subi des pertes multiples vivent un traumatisme (Bigelow & Hollinger 1996;Cadell 2001Cadell , 2003Cadell, Regehr & Hemsworth 2003;Gluhoski, Fishman & Perry 1997a, 1997bGoodkin et al 1996;Houseman & Pheifer 1988;Martin & Dean 1993;Sikkema, Kalichman, Kelly & Koob 1995). L'hétérosexisme et l'homophobie peuvent ajouter à la stigmatisation aussi bien qu'à une augmentation du stress.…”
Section: Introductionunclassified